C. difficile PCR-ribotype 023 might go undetected when using ChromId C. difficile agar. (April 2017) - Reigadas, E.; Alcalá, L.; Marín, M.; Martín, A.; Bouza, E.
Abstract: We compared the performance of the new chromogenic medium ChromID C. difficile with that of CLO agar. ChromID C. difficile agar is a sensitive medium that can accelerate the presumptive identification of C. difficile, however ribotype 023 might go undetected when using this chromogenic medium.